KONSEP KESEIMBANGAN HIDUP DALAM PERSPEKTIF AL QURAN - Ali Ashar Ali Ashar (Al Fattah Ejournal Sma Al Muhammad Cepu, 2023)
The concept of life balance that is packaged by the Koran is stronger, intact and perfect because between God, humans and nature connected, between the senses, reason and heart work, between spiritual and material with each other, between individuals and society walking together between world and the hereafter Mutual useful. Researchers are interested in examining the concept of balance in the perspective of the Koran with the aim of finding out how the concept of balance is regulated and described in the Holy Qur'an. Research uses a literature research approach by reviewing previous books and research that are relevant to the main points of discussion and problems of the analysis of a reference obtained from the desired data in depth. Al Quran various concepts of balance related to human life and their development in the history of civilization. The concept includes a balance between rights and obligations, law and justice, deeds and reply, the balance of the universe, the relationship with God and humans, to the balance between world life and the hereafter. The concepts of the balance are reinforced by the long history of Islamic civilization to the fields of kalam science, fiqh, philosophy, and Sufism.